ENGLISH TEACHER'S AUTONOMY IN THE INSTRUCTIONAL PLANNING DECISION-MAKING IN INDONESIAN SECONDARY SCHOOLS - Intifadhah, - (2019)
Teachers' autonomy in designing their instructional documents is essential for students' learning engagement. It provides teachers with a large control over the choice of teaching methodologies and activities, selects or design their own tasks and materials, and evaluate outcomes so that teachers can maximize their ability to develop their teaching creativity for the betterment of students' learning. This study aimed to investigate the degree of English teachers' autonomy in instructional planning decision-making in secondary schools and factors that facilitate and constrain the development of teacher autonomy. A qualitative study with case study design and two-stage qualitative analysis procedure was employed in this study. Involving thirty English teachers from MGMP program and three selected teachers from senior high schools among thirty, this study utilized the questionnaire, interview, document analysis, and classroom observation. The findings showed that more than half of the teachers (63%) attained a high degree of autonomy while 37% of teachers gained a moderate degree of autonomy and none of the teachers had a low degree of autonomy. The degree of teacher autonomy in curricular autonomy domain was in a moderate degree (56.5%). Meanwhile, the degree of teacher autonomy in instructional autonomy and assessment procedure was relatively in a high degree (73% and 70%). Moreover, there were three external factors that facilitate teachers' autonomy, including job satisfaction, working condition, and school climate. Teachers' self-empowerment was indicated as the internal factor that facilitates teachers' autonomy. There were four external factors that constraint teachers' autonomy. These include educational policy and institutional requirements, lack of time, classroom complexity, and the variation of students' needs and characteristics. The issues related to teachers' personal attitude and lack of self-empowerment were identified as the internal factors that constrain teachers' autonomy. In addition, it is suggested for the authorities to be more aware of the importance of giving the teachers the opportunity to modify the curriculum based on teaching and learning process and provide the necessary conditions for teachers to develop their autonomy in instructional plan and process. Keywords: Domains of teacher autonomy, External and internal factors, Instructional planning decision-making, Teacher's autonomy. ------- Otomoni guru dalam merancang dokumen pengajaran sangat penting untuk meningkatkan keterlibatan siswa dalam proses belajar. Dalam hal ini, guru diberikan keleluasaan dalam memilih metodologi dan kegiatan pengajaran, merancang bahan ajar mereka sendiri dan mengevaluasi hasil pembelajaran, sehingga guru dapat memaksimalkan kemampuan mereka dalam mengembangkan kreativitas mengajar mereka. Penelitian ini bertujuan untuk menginvestigasi tingkat otonomi guru Bahasa Inggris dalam pengambilan keputusan yang berhubungan dengan perencanaan pengajaran di sekolah menengah dan faktor-faktor yang memfasilitasi dan menghambat pengembangan otonomi guru. Penelitian ini merupakan penelitian kualitatif dengan studi kasus dan menggunakan dua tahap prosedur analisis kualitatif. Melibatkan tiga puluh guru Bahasa Inggris dari program MGMP dan tiga guru yang dipilih dari sekolah menengah atas, penelitian ini menggunakan kuesioner, wawancara, analisis dokumen, dan observasi kelas sebagai instrument penelitian. Hasil dari penelitian ini menunjukkan bahwa lebih dari separuh guru (63%) mencapai tingkat otonomi tinggi sementara 37% guru memperoleh tingkat otonomi sedang dan tidak ada guru yang memiliki tingkat otonomi yang rendah. Tingkat otonomi guru pada curricular autonomy berada pada tingkat sedang (56,5%). Sementara itu, tingkat otonomi guru pada instructional autonomy dan assessment procedure relatif tinggi (73% dan 70%). Selain itu, terdapat tiga faktor eksternal yang memfasilitasi otonomi guru yaitu kepuasan dalam bekerja, kondisi kerja, dan iklim sekolah, sedangkan pemberdayaan diri guru merupakan faktor internal yang memfasilitasi otonomi guru. Terdapat empat faktor eksternal yang menghambat otonomi guru yaitu kebijakan pendidikan dan persyaratan kelembagaan, kurangnya waktu, kompleksitas kelas, dan variasi kebutuhan dan karakteristik siswa. Masalah yang terkait dengan sikap pribadi guru dan kurangnya pemberdayaan diri guru merupakan faktor internal yang menghambat otonomi guru. Oleh karena itu, penulis menyarankan agar otoritas sekolah dapat lebih menyadari pentingnya memberikan guru kesempatan untuk memodifikasi kurikulum berdasarkan proses belajar mengajar dan menyediakan kondisi yang diperlukan bagi guru untuk mengembangkan otonomi mereka dalam rencana dan proses pengajaran. Kata kunci: Faktor eksternal dan internal, Pengambilan keputusan dalam perencanaan pembelajaran, Otonomi guru.